Competencies of master teachers of La Union in conducting action researches : basis for an action plan - Llavore, Erwin C. (Dagupan City : [s.n.], 2017)
This study is entitled "Competencies of Master Teachers of La Union in Conducting Action Researches: Basis for an Action Plan". It aimed to improve the competencies of master teachers of La Union in conducting action researches. This study assessed the competencies of Master Teachers in the province of La Union in conducting action researches as a basis for proposing an action plan.
Bibliography: pages 138-149.
CHED-La Union
Keywords: Teachers